International Relations: State-Driven and Citizen-Driven Networks. (April 2014) - Crooks, Andrew; Masad, David; Croitoru, Arie; Cotnoir, Amy; Stefanidis, Anthony; Radzikowski, Jacek
The international community can be viewed as a set of networks manifested through various transnational activities. The availability of longitudinal data sets such as international arms trades and United Nations General Assembly (UNGA) allows for the study of state-driven interactions over time. In parallel to this top-down approach, the recent emergence of social media is fostering a bottom-up and citizen-driven avenue for international relations (IRs). The comparison of these two network types offers a new lens to study the alignment between states and their people. This article presents a network-driven approach to analyze communities as they are established through different forms of bottom-up (e.g., Twitter) and top-down (e.g., UNGA voting records and international arms trade records) IRs. By constructing and comparing different network communities, we were able to evaluate the similarities between state-driven and citizen-driven networks. In order to validate our approach we identified communities in UNGA voting records during and after the Cold War. Our approach showed that the similarity between UNGA communities during and after the Cold War was 0.55 and 0.81, respectively (in a 0–1 scale). To explore the state- versus citizen-driven interactions, we focused on the recent events in Syria within Twitter over a sample period of 1 month. The analysis of these data show a clear misalignment (0.25) between citizen-formed international networks and the ones established by the Syrian government (e.g., through its UNGA voting patterns).